Work Outcome Preferences of Muslim and Jewish Managers in Israel: Analyzing the Differences According to the Individualism-collectivism Model - Sharabi, Moshe; Shdema, Ilan; Abboud-Armaly, Oriana (Journal of Ethnic and Cultural Studies, 2023)
While there is an increasing number of Muslim managers in Western countries, to the best of our knowledge no study has compared their work values to those of managers of other religions. The present study compares work outcome preferences (WOPs) of Muslim and Jewish managers in Israel, a Western country where Muslims constitute a substantial but marginalized minority. The methodology involves questionnaires administrated to 100 Muslim and 253 Jewish managers. The findings indicate significant differences between Muslim and Jewish managers across all work outcome preferences examined. While both groups view income as the most important value, Muslims have emphasized, in addition, serving society and status and prestige, whereas among Jews interest and satisfaction and interpersonal connections are more highly valued. The value differences between the two ethnoreligious groups can be explained mainly by cultural differences – individualism vs. collectivism. Implications are discussed in the context of labor market integration of minorities.